Voices to be heard: Understanding family perspectives in forensic care trajectories - Rowaert, Sara; De Pau, Marjolein; De Meyer, Florian; Nicaise, Pablo; Vander Laenen, Freya; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2022)
Introduction De-institutionalization of psychiatric care has greatly increased the role of family members in the recovery pathways of Persons labeled as Not Criminally Responsible (PNCR). However, the role of family members in supporting PNCR in forensic psychiatric care remains understudied. Scarce evidence indicates that PNCR have to deal with stigma and endure specific burdens (i.e., symptom-specific, financial, social, and emotional). Recovery-focused research showed that recovery in both persons with a severe mental illness and family members develop in parallel with each other and are characterized by similar helpful principles (e.g., hope and coping skills). As such, the recovery pathways of PNCR often goes hand in hand with the recovery pathway of their family members. During the family recovery process, family members often experience not being listened to or being empowered by professionals or not being involved in the decision-making process in the care trajectory of their relative. Therefore, the aim of this study is to capture how family members experience the care trajectories of their relatives, more specifically by looking at family recovery aspects and personal advocacy of family members. Methods Semi-structured interviews were conducted with 21 family members of PNCR from 14 families. A thematic analysis confirms that family members suffer from stigma and worry significantly about the future of their relative. Results Regarding the care trajectory of PNCR, family members experienced barriers in multiple domains while trying to support their relative: involvement in care and information sharing, visiting procedures, transitions between wards, and the psychiatric and judicial reporting by professionals. In addition, family members emphasized the importance of (social) support for themselves during the forensic psychiatric care trajectories and of a shared partnership. Discussion These findings tie in with procedural justice theory as a precondition for family support and family recovery within forensic psychiatric care.